Quantitative Investigation of Students’ Perceptions regarding Code Switching in Pakistani English Classrooms at University Level - Tabbasum, Raina (JELLL, 2023)
Code-switching is the focus of this study, illuminating its implications for communication, cultural identity, and pedagogical methods in Pakistani English classrooms. It emphasizes the importance of teachers recognizing and capitalizing on code-switching as a technique of bridging language and cultural gaps for the benefit of their students' education. This study investigates how students in Pakistani English courses feel about teachers' use of code-switching in the class. The university students at Institute of Space and Technology Islamabad were the population of this study. Purposive sampling technique was used for the collection of data from the sample. For sample, 100 university students of English course were collected from the population. Self-made questionnaire was developed for this study. The researcher collected the data face to face through a close ended questionnaire. The collected data was analyzed through the Statistic tool SPSS. The findings show that people see code-switching positively as a means to improve their communication skills. Code-switching is a socio-cultural manifestation, and respondents credit it to the preservation of their cultural identity. The results of the research highlight the importance of educators in influencing their students' views on code-switching. Findings show that the students feel more comfortable when they do code switching because they can understand things easily in their language like difficult sentences, vocabulary etc. This study has far-reaching effects on how we plan and execute instruction. The study recommends that the student and teacher should minimize the use of code switching in class. Teacher knows that the medium of instruction is English and they stop students to use a lot of code switching in class. A more welcoming and culturally sensitive classroom may be created when teachers are aware of code-switching as a communication method.